Number 46 (December 2003) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2003)
(December 2003) - Fish survey and bioassessment of Station Camp Creek in the Upper Kentucky River Drainage. By Jeffery M. Ray and Patrick A. Ceas Minutes, Business Meeting, 29th Annual Meeting, Southeastern Fishes Council
Keywords: fishes; survey; bioassessment; station camp creek; upper kentucky; river; drainage